Immigration Island, Port of Spain, Picturesque Trinidad - (:unkn) unknown (Bonanza Smith Bros. and Co.,[Trinidad and Tobago], 2011)
The postcard shows Nelson Island which belong to the group of "five islands" which are actually a group of six islands that are located west of Port of Spain, the capital of Trinidad, in the Gulf of Paria. Nelson Island is famous as the disembarkation point and quarantine station for indentured immigrants to Trinidad and Tobago.
Colour: Black, white and red; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; Emigration and immigration